Cover Image. Issue 18 (17th November 2021) - Müller, Nils C. J.; Kohn, Nils; van Buuren, Mariët; Klijn, Nadia; Emmen, Helene; Berkers, Ruud M. W. J.; Dresler, Martin; Janzen, Gabriele; Fernández, Guillén
Abstract : COVER ILLUSTRATION Schema memory board used to test object‐location associations during learning and during recall in the MRI scanner.